ANALISIS HUBUNGAN PELAYANAN APARATUR DESA DENGAN KEPUASAN MASYARAKAT DI DESA RUMAMIS KECAMATAN BARUS JAHE - Menanti Sembiring; Ingan Ukur Sitepu (JURNAL REGIONOMIC, 2021)
Public service is a series of activities in the context of fulfilling service needs inaccordance with the laws and regulations for every citizen and resident of goods, servicesand/or administrative services provided by public service providers. The villagegovernment is one of the parties that has duties and responsibilities in providing servicesto the community. The purpose of this study was to determine the relationship betweenvillage apparatus services and community satisfaction in Rumamis Village, Barus JaheDistrict. Data was collected using observation, interview, and questionnaire techniques.The analysis technique used is descriptive analysis and Rank Spearmans correlationanalysis. The results showed that there was a positive and significant relationshipbetween village apparatus services and community satisfaction in Rumamis Village,Barus Jahe District.